Nonlinear Effects of Inflationon Economic Growth - Sarel, Michael (Washington, D.C. : International Monetary Fund, 1995)
This paper examines the possibility of nonlinear effects of inflation on economic growth. It finds evidence of a significant structural break in the function that relates economic growth to inflation. The break is estimated to occur when the inflation rate is 8 percent. Below that rate, inflation does not have any effect on growth, or it may even have a slightly positive effect. When the inflation rate is above 8 percent, however, the estimated effect of inflation on growth rates is significant, robust and extremely powerful. The paper also demonstrates that when the existence of the structural break is ignored, the estimated effect of inflation on growth is biased by a factor of three.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Effect Of Inflation; Growth Rate; Inflation Coefficient; Terms Of Trade Data; WP; New Zealand